2007
DOI: 10.1242/jeb.002741
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid availability does not limit the capability of nestling kestrels (Falco tinnunculus) to cope with oxidative stress

Abstract: There was no effect on ROMs, OXY or the level of oxidative stress (ratio between ROMs and OXY), however, or on body mass or body condition of nestlings. ROMs and OXY decreased with age, but this pattern varied across the nests. Our results show that (i) in general, younger nestlings actually have to cope with a high free radical production, and (ii) the ability of wild nestling kestrels to cope with oxidative stress is not affected by carotenoid availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 54 publications
(68 reference statements)
2
27
0
Order By: Relevance
“…Carotenoids are also considered as dietary antioxidants, occur as natural pigments in fish and birds, and are important for processes of sexual selection (Hill, 1991) and parent-offspring interactions (Saino et al, 2000). Recently, the importance of carotenoids as antioxidants in vivo has been debated because an increasing number of field experiments could not prove a direct effect of carotenoids on oxidative stress (Hõrak et al, 2006;Costantini et al, 2007;Isaksson et al, 2007;Larcombe et al, 2010). Additionally, Costantini and Møller (Costantini and Møller, 2008) showed in a meta-analysis that carotenoids are only minor antioxidants for birds.…”
Section: Research Articlementioning
confidence: 99%
“…Carotenoids are also considered as dietary antioxidants, occur as natural pigments in fish and birds, and are important for processes of sexual selection (Hill, 1991) and parent-offspring interactions (Saino et al, 2000). Recently, the importance of carotenoids as antioxidants in vivo has been debated because an increasing number of field experiments could not prove a direct effect of carotenoids on oxidative stress (Hõrak et al, 2006;Costantini et al, 2007;Isaksson et al, 2007;Larcombe et al, 2010). Additionally, Costantini and Møller (Costantini and Møller, 2008) showed in a meta-analysis that carotenoids are only minor antioxidants for birds.…”
Section: Research Articlementioning
confidence: 99%
“…The antioxidant property of carotenoids is, however, part of an ongoing debate (Costantini et al, 2007;Costantini and Moller, 2008;Hartley and Kennedy, 2004;Isaksson et al, 2007). There is a wide heterogeneity among studies that have explored the antioxidant nature of carotenoids.…”
Section: Immune Activation and Carotenoids Allocationmentioning
confidence: 99%
“…Nevertheless, it is important to keep in mind that the physiological properties of these pigments are currently under debate, since not all studies have provided support for the antioxidant function of carotenoids in vivo (Costantini and Moller, 2008;Hartley and Kennedy, 2004;Isaksson et al, 2007). For instance, Pike et al (Pike et al, 2007) have shown that carotenoid-supplemented male sticklebacks (Gasterosteus aculeatus) have a more exuberant nuptial coloration, a better survival rate, a higher reproductive output, and, more importantly, a reduced level of oxidative stress compared with control individuals, whereas Costantini et al (Costantini et al, 2007) did not report any effect of carotenoid supplementation on oxidative stress of nestling kestrels (Falco tinnunculus). It is not immediately clear why different studies have reported different results.…”
Section: Introductionmentioning
confidence: 99%
“…Pennycuick, 1968;Rothe et al, 1987;John et al, 1988;Bordel and Haase, 1993;Bordel and Haase, 2000;George and John, 1993;Schwilch et al, 1996). To quantify the oxidative status of this species, we determined, (1) the oxidative damage as serum reactive oxygen metabolites (ROMs; primarily hydroperoxides) and (2) the total (Costantini et al, 2006;Costantini et al, 2007a;Costantini et al, 2007b). Given that high activity levels may increase free radical production, we expected to find a positive association between flight time and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%